Nitrifying soil bacterium Nitrosomonas europaea: operational improvement of standard culture medium - Padrão, Jorge (2019)
Nitrosomonas europaea is the most extensively studied ammonia-oxidizing bacterium (AOB), being a ubiquitous player in the conversion of ammonia in the soil environment. The precipitation of constituents of the standard culture medium, American Type Culture Collection (ATCC) \#2265, further hinders both the study of N. europaea vital role in the nitrogen cycle and the development of biotechnological applications, as the presence of inorganic debris severely compromises scale-up procedures and downstream processing. The standard formulation was analyzed; the precipitate was identified as being struvite. Struvite is spontaneously formed when magnesium, phosphate, and ammonium are available in a high pH solution. This combination is common and transversal to a series of AOB media formulations. Therefore, a non-precipitating medium was developed. The modified medium does not require filter sterilization, which reduces 99\\% of its production cost. The kinetic performance of N. europaea was evaluated in the standard and modified medium. A precise and direct quantification of the bacterium cell growth profile was achieved using fluorescent in situ hybridization (FISH) and flow cytometry, which was correlated with other metabolic parameters. The performance of N. europaea was not impaired in the modified medium.